StaTips Part III: Assessment of the repeatability and rater agreement for nominal and ordinal data - Giuseppe Perinetti (Dentitio, 2017)
Assessment of the repeatability and rater agreement for nominal and ordinal data is an important procedure in medical research. This analysis applies to several cases including: i) replicate recordings by the same rater using the same parameter; ii) agreement between/ among raters using the same parameter; and iii) agreement between/among different parameters recorded by the same rater. Herein, the most common coefficients of agreement are presented along with criteria for their proper selection.